Effects of language experience, use, and cognitive functioning on bilingual word production and comprehension - Litcofsky, Kaitlyn A.; Tanner, Darren; Hell, Janet G. van (International Journal of Bilingualism, 2016)
Considerable research has investigated how bilinguals produce and comprehend words, focusing mainly on how bilinguals are able to select words from the appropriate language. Less research, however, has investigated whether production and comprehension involve the same underlying mechanisms. The present study explores this issue by examining whether production and comprehension, in the first language (L1) and second language (L2), are similarly influenced by factors relating to language experience, language use, and cognitive functioning. Results showed that (1) production and comprehension were more closely linked in L1 than in L2; (2) production in L1 and L2 was predicted by language proficiency; and (3) comprehension in L1 and L2 was predicted by working memory. This is the first study to compare lexical processing in production and comprehension in both L1 and L2 and how these processes are influenced by language experience, use, and cognitive factors.